Inference of future bog succession trajectory from spatial chronosequence of changing aapa mires. Issue 4 (18th April 2023) - Kolari, Tiina H. M.; Tahvanainen, Teemu
Abstract: Climate change‐driven vegetation changes can alter the ecosystem functions of northern peatlands. Several case studies have documented fen‐to‐bog transition (FBT) over recent decades, which can have major implications, as increased bog growth would likely cause cooling feedback. However, studies beyond individual cases are missing to infer if a common trajectory or many alternatives of FBT are in progress. We explored plant community and hydrology patterns during FBT of 23 boreal aapa mire complexes in Finland. We focused on mires where comparisons of historical (1940–1970) and new (2017–2019) aerial photographs indicated an expansion of Sphagnum ‐dominated zones. Vegetation plot and water chemistry data were collected from string‐flark fens, transition zones with indications of Sphagnum increase, and bog zones; thus, in a chronosequence with a decadal time span. We ask, is there a common trajectory or many alternatives of FBT in progress, and what are the main characteristics (species and traits) of transitional plant communities? We found a pattern of fen‐bog transitions via an increase in Sphagnum sect. Cuspidata (mainly S . majus and S . balticum ), indicating a consistently high water table. Indicators only of transitional communities were scarce ( Sphagnum lindbergii ), but FBT had apparently facilitated shallow‐rooted aerenchymatous vascular plants, especially Scheuchzeria palustris . Water pH consistently reflected the chronosequence with averages of 4.2, 3.9, and 3.8, from fen to transition and bog zones. Due to weak minerotrophy of string‐flark fens, species richness increased towards bogs, but succession led to reduced beta diversity and homogenization among bog sites. Decadal chronosequence suggested a future fen‐bog transition through a wet phase, instead of a drying trend. Transitional poor‐fen vegetation was characterized by the abundance of Sphagnum lindbergii, S . majus, and Scheuchzeria palustris . Sphagnum mosses likely benefit from longer growing seasons and consistently wet and acidic conditions of aapa mires. Abstract : We studied recent fen‐bog transitions and the characteristics of transitional plant communities in 23 boreal aapa mires in a spatial chronosequence with a decadal time span. We found a pattern of fen‐bog transitions via an increase in wet Sphagna ( Sphagnum lindbergii, S . majus, and S . balticum ) and Scheuchzeria palustris, highlighting the fact that under climate change, boreal fens may experience a shift to Sphagnum ‐dominated bogs through a wet phase.